To Study Inflation Impact in Malaysia Against the Stock Portfolio Investment in Bursa Malaysia - Yeoh, Wee Win (Interdisciplinary Social Studies, 2023)
Background: The rising of the inflation had triggered to need to choose the right investment to beat the inflation. The study will focus on the potential impact in investing in diversified stock portfolio within the stock market exchange in Bursa Malaysia. Aim: The goal of the research is target to understand the potential existence of the positive correlation and relationship between the KLSE market index and the inflation rate through the CPI. Method: The quantitative analysis method will be conducted to study the historical data based on the past 20 years’ trend of data from both inflation rate through CPI as well as the KLSE market index. The average yearly growth for the past 20 years performance will also be assessed to understand the comparison on the growth of the inflation and market index. Findings: The findings had observed that the investment for the portfolio investment representing through the KLSE market index had not been sharing the significant positive correlation and relationship with the inflation rate on CPI. However, the growth rate on average had obsvered higher rate of return on KLSE market index which is 5.666% over the inflation rate through CPI that recorded only 2.018% indicating that the investment in diversified stock portfolio will obsvered greater return to cover for the inflation rate in Malaysia.